2020
DOI: 10.1101/2020.11.25.398727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ArabidopsisbZIP11 is a susceptibility factor duringPseudomonas syringaeinfection

Abstract: The induction of plant nutrient secretion systems is critical for successful pathogen infection. Some bacterial pathogens, e.g. Xanthomonas species, use TAL (transcription activator-like) effectors to induce transcription of SWEET sucrose efflux transporters. Pseudomonas syringae pathovar (pv.) tomato strain DC3000 lacks TAL effectors, yet is able to induce multiple SWEETs in Arabidopsis thaliana by unknown mechanisms. Since bacteria require other nutrients besides sugars for efficient reproduction, we hypothe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Additionally, we found that four other transcription factors, JcbZIP11, JcERF106, JcRF2a and JcPAT1, all interact with the pyrimidine box. JcbZIP11 and JcRF2a are members of the bZIP transcription factor family, and their homologs in other species have been described to be involved in pathogen resistance (Dai et al 2004;Prior et al 2021). Homologs of JcERF106 and JcPAT1 have been reported to be involved in ethylene and JA signaling (Feng et al 2020;Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that four other transcription factors, JcbZIP11, JcERF106, JcRF2a and JcPAT1, all interact with the pyrimidine box. JcbZIP11 and JcRF2a are members of the bZIP transcription factor family, and their homologs in other species have been described to be involved in pathogen resistance (Dai et al 2004;Prior et al 2021). Homologs of JcERF106 and JcPAT1 have been reported to be involved in ethylene and JA signaling (Feng et al 2020;Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%